PENDEKATAN EDUPLAY PADA FASILITAS PEMBELAJARAN SEKOLAH DASAR DI BOJONG BARU, KABUPATEN BOGOR - Subagio, Angela; Solikhah, Nafiah (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
In 2045, Indonesia's population will be the golden generation. Therefore, children aged 6-12 years have an important role to prepare themselves in the crucial factor, education. One of the challenges in the education sector in Indonesia is the lack of adequate facilities. According to data from the Badan Pusat Statistik (BPS) in the 2019/2020 school year, only 14% of classrooms in Indonesia were in good and adequate condition. Based on BPS data, Bogor Regency is at the top of the list with 8,243 classrooms that are inadequate for learning on Java Island. Based on preliminary research conducted by the author in 2023, there are 5 elementary schools in Bojong Baru and these schools have no other facilities besides classrooms. Meanwhile, according to the 1945 Constitution Article 31, schooling is the need and right of every citizen. The purpose of this research is to produce design criteria for the design of educational spaces for elementary school children by adjusting the characteristics of children who still like to play, lively and creative with the eduplay approach. Through the eduplay approach to building and space design, it is expected to create a learning environment that is fun, interesting, can stimulate children's growth and development and can balance learning and playing activities. This eduplay approach can be applied to the entire building, both exterior and interior. Covering: interactive classrooms, facilities to indoor-outdoor play areas. Keywords: Bojong Baru; education; eduplay; elementary school; kabupaten Bogor Abstrak Pada tahun 2045, penduduk Indonesia akan menjadi generasi emas. Oleh karena itu, anak usia 6-12 tahun memiliki peran penting untuk mempersiapkan diri dalam faktor krusialnya, pendidikan. Salah satu tantangan pada sektor pendidikan di Indonesia adalah masih kurang memadainya fasilitas. Menurut data Badan Pusat Statistik (BPS) pada tahun ajaran 2019/2020, tersisa 14% ruang kelas di Indonesia yang dalam kondisi baik dan memadai. Berdasarkan data BPS, Kabupaten Bogor berada pada urutan teratas dengan jumlah 8.243 ruang kelas yang tidak memadai untuk pembelajaran di Pulau Jawa. Berdasarkan riset awal yang dilakukan oleh penulis pada tahun 2023, terdapat 5 sekolah dasar di Bojong Baru dan sekolah tersebut tidak memiliki sarana lain selain ruang kelas. Sedangkan, menurut UUD 1945 Pasal 31, sekolah merupakan kebutuhan dan hak setiap warga negara. Tujuan penelitian ini adalah untuk menghasilkan kriteria desain rancangan ruang pendidikan bagi anak sekolah dasar dengan menyesuaikan karakteristik anak yang masih suka bermain, lincah dan kreatif dengan pendekatan eduplay. Melalui pendekatan eduplay terhadap desain bangunan dan peruangan, diharapkan dapat menciptakan lingkungan belajar yang menyenangkan, menarik, dapat merangsang tumbuh kembang anak serta dapat menyeimbangkan kegiatan belajar dan bermain. Pendekatan eduplay ini dapat diterapkan pada seluruh bangunan, baik exterior maupun interior. Meliputi: ruang kelas yang interaktif, fasilitas-fasilitas hingga area bermain indoor-outdoor.